Analysis of Misconception of Elementary School Teacher Study Program UKI Toraja Lectures about Fraction - Topanus Tulak; Rubianus Rubianus; Waldi Rianto; Vanessa Stevania; Cindy Cindy (Universitas Muhammadiyah Enrekang, 2022)
. As a result of misconceptions, new knowledge will not be properly integrated into students' cognitive structures. If a student learns a new concept and processes it into the student's cognitive structure, which mixes with the concept, it can lead to improper understanding. Therefore, it is the misconception that needs to be understood before it can be acted upon. Understanding mathematical concepts is an important foundation for solving mathematical problems and everyday problems. With a good understanding of mathematical concepts, students will easily remember, use, and rearrange a concept that has been learned and can solve various variations of mathematics. Therefore, understanding the concept is used as one of the three aspects of assessment in learning mathematics. Fractions are basic mathematics material that must be reached by prospective elementary school teacher students. The complexity of this material sometimes results in errors that not only occur to students, but also occur to teachers. This research was conducted with the hope that after knowing the misconceptions of prospective elementary school teacher students, it can be considered for mathematics lecturers in designing and managing the learning process so that later it can improve the understanding of prospective elementary school teacher students in terms of concepts and strategies before teaching in elementary schools.